2019
DOI: 10.1038/s41598-019-48873-z
|View full text |Cite
|
Sign up to set email alerts
|

Extreme levels of fallout radionuclides and other contaminants in glacial sediment (cryoconite) and implications for downstream aquatic ecosystems

Abstract: Glaciers in most parts of the world are retreating, releasing water and sediments to downstream rivers. Studies have found elevated levels of fallout radionuclides (FRNs) and other contaminants in glacial sediments, especially cryoconite, in European glaciers and Greenland. However, there are no equivalent studies for glaciers in North America. We report concentrations of FRNs (i.e. 137 Cs, 210 Pb un and 241 Am) and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
6
26
0
Order By: Relevance
“…The reported activity levels in this study are extremely high and comparable to soil samples from nuclear incident and explosion sites (Steinhauser et al, 2014;Abella et al, 2019). Subsequent studies, carried out in different regions of the global cryosphere (Alps, Caucasus, Svalbard and Canada), corroborated the ability of cryoconite to accumulate radionuclides (Baccolo et al, 2017;Łokas et al, 2016Owens et al, 2019), with radioecological consequences concerning the presence of FRNs that extend to the proglacial areas (Łokas et al, 2017;Owens et al, 2019). In addition to FRNs, cryoconite has also been shown to accumulate other anthropogenic contaminants including heavy metals (Nagatsuka et al, 2010;Łokas et al, 2016;Baccolo et al, 2017;Singh et al, 2017;Huang et al, 2019), artificial organic compounds (Ferrario et al, 2017;Weiland-Bräuer et al, 2017) and microplastics (Ambrosini et al, 2019).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The reported activity levels in this study are extremely high and comparable to soil samples from nuclear incident and explosion sites (Steinhauser et al, 2014;Abella et al, 2019). Subsequent studies, carried out in different regions of the global cryosphere (Alps, Caucasus, Svalbard and Canada), corroborated the ability of cryoconite to accumulate radionuclides (Baccolo et al, 2017;Łokas et al, 2016Owens et al, 2019), with radioecological consequences concerning the presence of FRNs that extend to the proglacial areas (Łokas et al, 2017;Owens et al, 2019). In addition to FRNs, cryoconite has also been shown to accumulate other anthropogenic contaminants including heavy metals (Nagatsuka et al, 2010;Łokas et al, 2016;Baccolo et al, 2017;Singh et al, 2017;Huang et al, 2019), artificial organic compounds (Ferrario et al, 2017;Weiland-Bräuer et al, 2017) and microplastics (Ambrosini et al, 2019).…”
Section: Introductionsupporting
confidence: 74%
“…The formation of cryoconite holes is attributable to the dark color, and thus low albedo, of cryoconite, which enhances the absorption of solar radiation and locally increases ice melting to foster the development of holes in the ice surface. Due to its contribution to ice melting, its diverse composition and the role in biodiversity, cryoconite has been studied by a range of disciplines, including glaciology, microbiology, biogeochemistry and ecology (Takeuchi et al, 2001;Langford et al, 2010;Cook et al, 2015;Ferrario et al, 2017;Pittino et al, 2018a). More recently cryoconite has been the subject of renewed interest due to its ability to accumulate specific substances, including anthropogenic contaminants (Pittino et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Besides living organisms, cryoconite is known to concentrate pollutants such as contaminants and radionuclides 11,12 . This may represent a problem in the future, with a possible secondary release of these substances to the environment 13,14 .Cryoconite accumulated in cryoconite holes has a limited impact on glacier and ice sheet surface mass balance. Instead, the presence of distributed organic material on the margin of ice sheets recently motivated the formalization of the concept of "bioalbedo feedback" 15-17 .…”
mentioning
confidence: 99%
“…Besides living organisms, cryoconite is known to concentrate pollutants such as contaminants and radionuclides 11,12 . This may represent a problem in the future, with a possible secondary release of these substances to the environment 13,14 .…”
mentioning
confidence: 99%
“…After being accumulated at the surface of glaciers, cryoconite and its radioactive content are released by glaciers in association with meltwater. Preliminary results have shown that a fraction of cryoconite radioactivity is accumulated in proglacial areas, and pose a risk of potential ecological impacts (Łokas et al, 2014,2017Owens et al, 2019).…”
Section: Introductionmentioning
confidence: 99%